Marine Polysaccharide Sulfatases - Helbert, William (Frontiers in Marine Science, 2017)
Polysaccharides are the most abundant and the most complex organic molecules in the ocean. In contrast to land polysaccharides, many marine polysaccharides are highly sulfated; in particular, the cell walls of macroalgae harbor a high diversity of sulfated polysaccharides (carrageenans, agarans, fucoidans, ulvans, etc.). These sulfated polysaccharides, biosynthesized by macroalgal primary producers, represent an important food source for heterotrophic organisms. Their biodegradation requires a set of enzymes that can cleave the glycosidic linkages of the carbohydrate backbone (called glycoside hydrolases) and the sulfate ester groups (called polysaccharide sulfatases). This review first provides on overview of the current state of knowledge on the classification and mechanisms of sulfatases in general. Then, based on an exploration of marine genomic and metagenomics data that reveals the diversity of carbohydrate sulfatases, it focuses on strategies to predict these sulfatases. In particular, the modularity of sulfatases and their location in marine polysaccharide utilization loci (PUL) provide clues as to their potential substrates and can drive future functional assays. Finally, the review underscores the low number of currently biochemically characterized marine carbohydrate sulfatases (e.g. agarases, carrageenanases and fucose sulfatases). Bottlenecks encountered in studies on sulfatases likely lie in the difficulties in purifying them and producing them in heterologous systems.